Innovative leadership practices in public organizations: a study of Kaduna State Local Governments of Nigeria - Shafiu, Awwal Muhammad (2021)
This study investigates the innovative leadership practices in public organizations, by choosing Kaduna state local government (KSLG) as a case study. The study was due to inadequacy of literature, poor leadership and inadequate service delivery which characterize the public sector at all levels of governance in Nigeria. Thus, the key objectives of the study are to: explore the level of digitalization among KSLG leaders; identify methods that KSLG leaders employ to implement changes in the organization; determine the presence and influence of innovative leadership on service delivery in KSLG and investigate the challenges faced KSLG leaders in practicing innovative leadership. Qualitative method was adopted in both data collection and analysis. Semistructured interviews and observations were used by drawing twenty (20) interviewees purposively from key leadership positions that included KSLG and local government service commission in the study area. The data analysis was conducted using content and thematic analysis techniques, while NVivo-11 was used in the analysis that help in managing large amount of data, developing themes and sub-themes, and making categorization easier. The findings of the study revealed that KSLG frequently used technological tools such as computers and internet to discharge their duties. It was also discovered that KSLG faced challenges like inadequate training, lack of technical know-how, and infrastructural deficit. Furthermore, the study showed that there were some levels of inadequacies in policy formulation and implementation in form of technological reforms that would facilitate the adoption and implementation of technological tools and innovations to improve service delivery in KSLG. The study recommends that KSLG should ensure that technological tools are adequately provided and implemented to control operations and improve service delivery. Capacity building in form of training and retraining programmes should also be frequently facilitated to enable employees to easily adapt in utilizing sophisticated technologies for effective service delivery.